착유시스템 유형별 세척수의 발생량과 특성 - 최동윤; 곽정훈; 박치호; 정광화; 김재환; 유용희; 정만순; 한창배; 최홍림; Choi, D.Y; Kwag, J.H; Park, C.H; et al. (축산시설환경학회지, 2008)
The purpose of this study was to determine the effect of milking system type on milking center effluent production through the four seasons. Four different types of milking systems (Bucket, Pipeline, Tandem and Herringbone) were estimated, in duplicate, through the different seasons. The following conclusions can be drawn from this study. 1. The quantity of wastewater produced from Tandem and Herringbone milking systems were significantly larger than Bucket milking system (p<0.05). 2. The main wastewater production was from the washing of milking apparatus. Tandem and Herringbone milking systems produced 398.8 and $407.7{\ell}$/day of wastewater, respectively, for apparatus washing. These values were significantly higher than the other milking systems during the summer (p<0.05). 3. The average wastewater production from the various milking systems was $15.4{\ell}$/head/day. The quantity of wastewater production during summer ($16.4{\ell}$/head/day) season was higher than of the other seasons. 4. The highest level of $BOD_5$ ($906.4mg/\ell$) was produced from the washing of the parlor floor and the lowest level of $BOD_5$ ($212.4mg/\ell$) was produced from the washing of the udders of the cows. 5. The pH of dairy wastewater was in the range of $7.3{\sim}8.2$ and the average levels of $BOD_5$, COD, SS, T-N, and T-P were 731.2, 479.0, 751.6, 79.1, $14.7mg/\ell$, respectively. Following conclusions can be drawn from this experiment. The quantities of wastewater production from Bucket, Pipeline, Tandem and Herringbone milking system were 143.9, 487.9, 914.0, and $856.7{\ell}$, respectively. The average wastewater produced from the milking systems was $15.4{\ell}$/head per day. In order to effectively manage on the wastewater from milking systems, dairy farms need to consider the milking system type and farm size when determining the optimum wastewater treatment system. 본 시험은 젖소농가에서 보유하고 있는 여러가지 형태의 착유시스템에 대하여 계절별 세척수의 발생량과 이화학적 특성을 알아보고자 바켓식, 파이프라인식, 텐덤식, 헤링본식 등 착유시스템 유형별로 각각 3농가를 선정하여 계절별로 조사를 실시하였으며, 그 결과는 다음과 같다. 1. 착유시스템 유형별 세척수 발생량은 텐덤식과 헤링본식에서 많았으며 바켓식이 적었다 (P<0.05). 2. 착유작업별 세척수 발생량은 착유기 세척에 가장 많은 량의 세척수를 사용하였으며 여름철의 경우 텐덤식 $398.8{\ell}$, 헤링본식 $407.7{\ell}$가 다른 착유시스템보다 많은 세척수를 사용하였다 (p<0.05). 3. 착유과정에서 발생하는 세척수 발생량을 조사한 결과, 평균 $15.4{\ell}$/두였으며, 계절별로는 여름이 $16.4{\ell}$로 가장 많은 세척수가 발생되었다. 4. 착유과정에서 발생하는 세척수의 $BOD_5$는 착유실 세척시 발생하는 세척수가 $906.4mg/\ell$로 가장 높았으며, 유두 세척시 가장 낮은 $212.4mg/\ell$로 나타났다. COD, SS 등도 착유실 바닥세척시 가장 높은 경향을 보였다. 5. 세척수의 이화학적 특성은 pH는 $7.3{\sim}8.2$의 범위로 착유작업 단계에 따라 차이를 나타내었으며, 착유작업 후 착유실 외부로 흘러나오는 배출수의 $BOD_5$, COD, SS, T-N, T-P는 각각 731.2, 479.0, 751.6, 79.1, $14.7mg/\ell$였다. 이상의 시험결과를 종합해 보면 착유시스템 유형별 세척수 발생량은 바켓식, 파이프 라인식, 텐덤식 및 헤링본식이 각각 143.9, 487.9, 914.0, $856.7{\ell}$로 조사되었으며, 착유과정에서 발생하는 세척수량은 착유우 두당 $15.4{\ell}$로 착유시스템 유형 및 착유우 사육두수에 따라 낙농가도 농가실정에 맞는 세척수 처리시설 및 용량을 확보해야 할 것으로 판단된다.